‘QUO VADIS’ SISTEMATIESE TEOLOGIE? - Punt, J. 1962- (2009)
The essay provides five different responses to the question about the present state and future of systematic theology. Firstly, it refers to the widespread Trinitarian renaissance in theological circles. Secondly, systematic theology often responds to so-called contemporary challenges, which today, in different parts of the world, are often described in terms of the complex tensions between individual and collectivity, between authority and reason, and between past, present and future. Thirdly, systematic theology often reacts to the so-called spirit of the times, which again can be popularly depicted in terms of secularisms or spiritualities, postmodernisms or fundamentalisms, globalizations or ecological crises. Fourthly, systematic theology takes place in the form of several discussions, including an increasingly worldwide discussion; the discussion with different theological disciplines; the broader conversation within the academy; the discussions within public life; the conversation in and with the church; the many ecumenical conversations; and the ongoing conversation within the discipline itself. Finally, it is directed "towards God" - serving worship, spirituality, formation, pastorate, and ethics.
Keywords: Aqedah; Gender; Human Dignity; Power; Sacrifice; Violence